Preparation and Characterization of Protocatechuic Acid Sulfates - Sofia M. Gutierrez-Zetina; Susana Gonzalez-Manzano; Jose J. Perez-Alonso; Ana M. Gonzalez-Paramas; Celestino Santos-Buelga (Molecules, 2019)
Protocatechuic acid (3,4-dihydroxybenzoic acid; PCA) is a phenolic acid present in plants as a secondary metabolite and is also produced in the human organism as a metabolite from the degradation of polyphenols by the intestinal microbiota, particularly of flavonoids. However, PCA, like most polyphenols, is biotransformed in the human body to different conjugates as sulfates, which are found circulating in blood and could be involved in the bioactivity of the original compound. This paper describes a simple process for the preparation of PCA monosulfates with satisfactory yields. Two compounds were obtained that were identified as PCA-3-sulfate and PCA-4-sulfate by mass spectrometry and 1H and 13C nuclear magnetic resonance using one- and two-dimensional techniques (heteronuclear single-quantum coherence and heteronuclear multiple-bond correlation). Differential MS fragmentation behavior and UV spectra were observed for each compound, which could be used for their identification in samples of unknown composition. The described procedure can be used for the preparation of these polyphenol metabolites in view of their use in in vivo and in vitro studies, as well as standards for their analysis in biological fluids, to contribute to the elucidation of biological effects of dietary polyphenols.